Frequency of cytomegalovirus in fertile and infertile men, referring to Afzalipour Hospital IVF Research Center, Kerman, IRAN: A case-control study - Majid Mohseni; Hamid Reza Mollaei; Seyed Alimohammad Arabzadeh; Tooraj Reza Mirshekari; Peyman Ghorbani (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Cytomegalovirus (CMV) virus can hide in urinary genital tract cells and affect male infertility disorders. Objective: To evaluate frequency of CMV in the semen samples of men with infertility problems referring to a in vitro fertilization (IVF) center in Kerman, Iran and its association with the parameters of semen. Materials and Methods: In this case-control study, Real time polymerase chain reaction test was performed for detection of human cytomegalovirus in 100 fertile men compared to 100 infertile men referred to the IVF center of Afzalipour Hospital, Kerman, Iran. Results: Out of 200 samples, 30 samples (15%) were positive for CMV DNA virus (23/100 men (23%) in case group and 7/100 men (7%) in the control group). Sperm counts and motility in the control group were more than the case group (p˂0.0001). There was a significant relationship between the prevalence of CMV infection and male infertility (p˂0.001). Conclusion: Our finding showed that, prevalence of CMV infection was higher in infertile men compared to fertile men and CMV infection can be considered as an important part of male infertility. So; antiviral treatment of positive cases can be effective in improving sperm quality and successful IVF. The relationship between CMV infection in semen and infertility was obtained in previous studies and was confirmed by our study.